Omic applications to understand food system microbiomes - Jessica Gray (Microbiology Australia, 2022)
Understanding the microbial communities associated with food systems has traditionally used culture-based techniques that can provide a snapshot of the microorganisms present. However, this approach requires multiple media types and only allows for the identification of a limited number of culturable species. Culture-independent methods such as sequencing and omic techniques provide a deeper understanding of the microbial community, how they interact and function together across the entire food system. This review provides a brief introduction to omic techniques used in microbiome studies and touches on microbiome research that has been undertaken across the farm to fork continuum focusing on leafy vegetables where possible.